Study of Hatching Traits of Eggs of Local Chickens Raised in Basra Governorate - Sultan, Arshad T. M.; Al-Shaheen, Sajida A.; Ghani, Qutaiba J. (International Journal of Aquatic Research and Environmental Studies, 2026)
The aim of this study was to investigate the effect of feather color on hatchability parameters of three genetic groups of local chickens raised in Basra governorate. The study included field visits to local chicken flocks available to breeders in different areas of Basra governorate. This study was conducted to determine the effect of feather color on hatching parameters of three genetic groups of local chickens during initial period of egg production (24-28 weeks) and during peak egg production period (44-46 weeks). The results of hatching parameters during initial period of egg production showed no significant (p≤ 0.05) differences in eggs weights (g) between local chicken groups according to different feather colors (white, black and brown). A significant (p≤ 0.05) superiority was observed in fertility rate (%) of local white feather chicken group (LW) compared to local brown feather chicken group (LBR). The results showed that local black feather chicken group (LB) was significantly (p≤ 0.05) superior in hatchability rate (%) compared to the groups of local white (LW) and brown (LBR) chickens. The results also showed a significant (p≤ 0.05) increase in embryonic mortality rate (%) for the local white (LW) and brown (LBR) chicken groups compared to the local black (LB) chicken group. The local chicken genotypes did not differ significantly (p≤ 0.05) in the weight of the hatched chick during initial egg production period. The results of the hatching parameters during peak egg production showed no significant (p≤ 0.05) differences between local chicken groups in eggs weight (g), fertility rate (%), hatchability rate (% ), embryonic mortality rate(% ) , and hatched chick weight (g). This study demonstrates the independence of genes responsible for feather color from genes related to egg weight and hatching chick weight.